Analisis Quality Of Service (QoS) Pada Jaringan Internet (Studi Kasus: Kebun Raya Purwodadi – BRIN) - Rachmawan Adi Laksono; Heri Apriyanto; Aldiansa Kautsar (Universitas PGRI Kanjuruhan Malang, 2022)
A good network service must pay attention to the services provided to its users. When you want to build a network, the main factor that should be considered is Quality of Service (QoS). QoS is a method for measuring how good the quality of a network service is. The QoS parameters are throughput, packet loss, delay, and jitter according to the Telecommunications and Internet Protocol Harmonization Over Network (TIPHON) standard. Purwodadi Botanical Gardens uses an Internet Service Provider (ISP) from PT Indonesia Comnets Plus (Icon +) and the leased bandwidth is 20 MBps. The Purwodadi Botanical Gardens provides many hotspot networks to make it easier for employees to do their jobs. Therefore, measurements are needed to find out how good the quality of the network services provided is. The measurement results from QoS at several hotspots in Purwodadi Botanical Gardens get results with a throughput value of